Geometric Features of a Multilayer Surface After Water Jet Cutting in Variable Cutting Conditions - Lelen, Michal; Ruggiero, Alessandro; Jozwik, Jerzy (Manufacturing Technology Journal, 2023)
The paper presents the results of experimental work on the assessment of 3D geometry of surface stereometry obtained as a result of Water Jet (AWJ) water-abrasive beam cutting using an Eckert Opal WaterJet COMBO hydro-abrasive cutter. Studies of geometric structures were conducted using the Alicona Infinite Focus microscope. The article analyses selected spatial roughness parameters of the multilayer structure surfaces combined as a result of the vulcanization process with an aluminium alloy surface. The results of the research work are summarized in the technological function of the WJ cutting conditions, such as the cutting speed and the mass flow of the abrasive material.
Keywords: Aluminium alloy; Microscopic analysis; Water Jet cutting; Surface morphology; Tribology